Role of Built Environments on Physical Activity and Health Promotion: A Review and Policy Insights - Zhong, Jingjing; Liu, Wenting; Niu, Buqing; Lin, Xiongbin; Deng, Yanhua (Frontiers in Public Health, 2022)
As urbanization and motorization continue worldwide, various health issues have emerged as a burden between individuals, families and governments at all levels. Under the prevalence of chronic disease, this review synthesizes research on the impact of the various built environments on the multiple health outcomes from a methodological and mechanistic perspective. Besides, it attempts to provide useful planning and policy implications to promote physical activity and health benefits. The finds show that: 1) Current literature has used a variety of dataset, methods, and models to examine the built environment–health benefit connections from the perspective of physical activity; 2) The prevalence of chronic diseases is inextricably linked to the built environment, and policy interventions related to physical activity as well as physical and mental well-being should be emphasized; 3) The impact of the various elements of built environments on health condition is manifested in the way influencing the lifestyle of residents, such as active travel and other types of physical activities; 4) Given the connections between various built environments and public health, the sectors of urban planning and the public health should strengthen a close cooperation to promote urban public health of residents. Finally, it proposes potential policy insights for urban planning and development towards a healthier city and society.